Liberalism and retreat from the continuation of its illuminational principles - األستاذ الدكتور رشيد عمارة ياس; المدرس محمد صابر كريم (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The Enlightenment had been like strong and revolutionary storm basic overwhelm of all ideas, principle, tradition and values which seeded and disseminate by the feudal constituents and Catholic church, throughout med century which knowing in().Thus this movement which had knowing as Enlightenment philosophical movement, paved the way to stand the new center, which nourished and provided with new value and principle standing on the Enlightenment's essential aims or goals which would relating with rationalism, progressive and liberty, that’s in order to liberating the human and to return its suitable dignity, and making him owner of himself. Confidently the Enlightenment caused a giant and revolutionary changing in all live sphere in those society which taken it, so with through this changing proses many philosophy and ideal paradigm and tendency had been emerging and rising, and such society and political tendency which binging working on continue that humanity progressive and revolutionary project. Liberalism, beside the French materialist paradigm, was one important of these tendency. However and in spite of that the liberalism, especially the classical paradigm of it, and in its first stage, had been illustrate its enforcement and skill in its efforts to achieve that real goals of Enlightenment, especially the individual liberty case, but all Liberalism tendency commence and fulfill attempts in ideal and philosophy level in order to really and dynamical incorporation for Enlightenment value and principles in its movements, had been clashing with aims and desires which dissenting from its sociality political trend which represented by Brogues class, contradicted entirely with those essential goals or values and principles for Enlightenment Philosophy.